1993
DOI: 10.1007/bf00197667
|View full text |Cite
|
Sign up to set email alerts
|

Angle measurements of the distal radius: a cadaver study

Abstract: The quality of reduction of distal radius fractures is assessed mainly by degree of restoration of radial angle and palmar tilt. This cadaver study investigates the effects of forearm rotation of these measurements. A 5 degree rotational change produces a 1.6 degree change in palmar tilt on the conventional lateral view and a 1.0 degree change on the 15 degree lateral view. Lateral radiographs could be rotated 15 degrees-30 degrees and still be considered acceptable. Therefore, rotation may produce up to a 4.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 4 publications
0
36
0
Order By: Relevance
“…Cadaveric studies indicate that 10°of supination of the distal radius increases the apparent volar tilt by approximately 5°. 12 Johnson and Szabo 25 found that a 15°lateral view may eliminate some of the variation in this measurement. Although the radiographic measurements performed in this study were based on true lateral 15°tilted radiographs, the only way to document truly whether the distal radius healed in a malrotated position relative to the shaft of the radius would have been with a computed tomography scan, which was not available for these patients.…”
Section: Discussionmentioning
confidence: 91%
“…Cadaveric studies indicate that 10°of supination of the distal radius increases the apparent volar tilt by approximately 5°. 12 Johnson and Szabo 25 found that a 15°lateral view may eliminate some of the variation in this measurement. Although the radiographic measurements performed in this study were based on true lateral 15°tilted radiographs, the only way to document truly whether the distal radius healed in a malrotated position relative to the shaft of the radius would have been with a computed tomography scan, which was not available for these patients.…”
Section: Discussionmentioning
confidence: 91%
“…Several investigators have performed cadaver studies in which angled radiographs have been used to determine articular displacement after experimentally created fractures. 7,8 Johnson and Szabo performed a cadaveric study in which they recommend a 15°angled lateral radial-to-ulnar radiograph be used to better assess distal radius angulation. 7 Ebraheim, in a case report, suggested that the x-ray beam be angled at 30°to assess the distal radial articular surface after dorsal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented that the frontal plane inclination of the distal radius lies between 19°and 29°(mean, 23°), 15 and that standard lateral radiographs obtained with an x-ray beam tangential to the articular surface may better portray the articular anatomy. [7][8][9][10]16 In the present study, ATL radiographs were better than standard lateral radiographs in terms of interobserver and intraobserver reliability.…”
Section: Discussionmentioning
confidence: 78%